Florida Container Mosquitoes: ENY860/IN851, 6/2010 - Rey, Jorge R.; Connelly, C. Roxanne Rutledge (EDIS, 2010)
ENY860, a 5-page illustrated fact sheet by Jorge R. Rey and Roxanne Connelly, describes common characteristics of these species of mosquito that develop in water-holding containers, both natural and artificial, major species in Florida, and methods of control. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.